Method for catalyzing dehydrogenation of methylcyclohexane by using high-entropy alloy supported catalyst
By using Ni-Cu-Fe-Co/SiO2 catalyst, the problem of low conversion rate of the nickel-copper system dehydrogenation catalyst in the dehydrogenation process of methylcyclohexane is solved, and the effect of efficient catalyzing of methylcyclohexane is achieved, which improves the conversion rate and selectivity, and maintains a stable hydrogen release rate.
Patent Information
- Application Number
- CN202311256200.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-26
- Publication Date
- 2025-03-28
AI Technical Summary
The existing nickel-copper system dehydrogenation catalyst has high selectivity but low conversion rate in the dehydrogenation process of methylcyclohexane, making it difficult to meet the needs of efficient catalysis.
The active components are supported by equal volume impregnation method and prepared by high-temperature calcination and hydrogen reduction to improve the supported active sites and surface structure of the catalyst and enhance the catalytic effect.
The conversion rate of methylcyclohexane was improved to 90.47%, the selectivity of toluene reached 92.82%, and a stable hydrogen release rate was maintained, reaching 102.4 mmol g-1h-1.
Smart Images

Figure CN119707618A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalytic dehydrogenation and relates to a method for dehydrogenating methylcyclohexane using a high entropy alloy supported catalyst. Background Art
[0002] There are many challenges in the transportation and storage of green hydrogen. Liquid organic hydrogen storage (LOHC) is a promising new solution to these challenges. The use of liquid organic hydrides in hydrogen storage has technical, economic and environmental advantages. When hydrogen is stored in a liquid organic hydrogen carrier, it can be transported over long distances. Since LOHC is liquid at room temperature and exhibits similar properties to crude oil-based liquids (such as diesel and gasoline), it can be easily handled, transported and stored; therefore, this technology can be gradually implemented using existing crude oil infrastructure. One of the most promising organic cycles for hydrogen storage is the MTH cycle consisting of methylcyclohexane (MCH), toluene and hydrogen. MCH stands out among many organic liquid hydrogen storage materials due to its low dehydrogenation toxicity, high hydrogen storage capacity and low cost. Chiyoda Corporation has developed the "SPERA HydrogenTM" system for large-scale hydrogen storage and transportation technology through a pilot plant demonstration using the MTH cycle, while my country's hydrogen storage technology is in its infancy. The key technology of the "SPERAHydrogenTM" system is to develop a new dehydrogenation catalyst that produces hydrogen at the hydrogen utilization site after transportation. Because the dehydrogenation of this technology is highly endothermic and the catalyst is easily coked and deactivated, it is crucial to design a catalyst with stable MCH dehydrogenation performance.
[0003] Many studies have focused on developing stable and active dehydrogenation catalysts, mainly based on platinum or other noble metals supported by alumina. Nevertheless, the high cost of noble metals has prompted researchers to reduce their use (especially platinum) and look for alternatives. Therefore, many efforts have been made to replace noble metals. In this context, cost-effective and widely used nickel-based catalysts have proven to be promising. However, monometallic nickel-based catalysts have low selectivity and stability in the dehydrogenation process, resulting in reduced hydrogen yield. The introduction of copper can significantly reduce the activity of nickel in hydrogenolysis conversion. For example, when using Ni-Cu bimetallic catalysts in cyclohexane dehydrogenation, the selectivity of toluene is significantly improved (up to 99%) compared with the monometallic nickel-based system, but the conversion of methylcyclohexane is reduced. Yuliya K. (Catalysts 2020, 10, 1198) synthesized a copper-modified nickel catalyst using heterogeneous sol-gel technology, which significantly improved toluene selectivity and yield, but the conversion of methylcyclohexane was not significantly improved. The catalyst with 80 wt% Ni and 20 wt% Cu showed 40% and 75-80% methylcyclohexane conversion rates at 96% and 89% toluene selectivity, respectively. There is still much room for improvement in the conversion rate of methylcyclohexane. Summary of the invention
[0004] The purpose of the present invention is to solve the problem that the nickel-copper system dehydrogenation catalyst in the prior art has high selectivity and low conversion rate, and to provide a method for efficiently catalyzing the dehydrogenation of methylcyclohexane using a high entropy alloy supported catalyst.
[0005] The technical scheme adopted by the present invention is: using a fixed bed reactor, gasifying methylcyclohexane and then passing it into a catalyst bed under the drive of nitrogen, 2 A dehydrogenation reaction is carried out under the action of a catalyst to obtain toluene and hydrogen.
[0006] The above Ni-Cu-Fe-Co / SiO 2 The catalyst is SiO 2 The catalyst is prepared by using Ni as a carrier, adopting an equal volume impregnation method to load active components Ni, Cu, Fe, Co and an auxiliary agent K, and undergoing high temperature calcination and hydrogen reduction. Taking the mass of the catalyst as 100%, the loading amount of Ni is 10% to 30%, the loading amount of Cu is 1% to 3%, the loading amount of Fe is 0.5% to 1.5%, the loading amount of Co is 0.5% to 1.5%, and the loading amount of K is 0.05% to 0.15%.
[0007] The above Ni-Cu-Fe-Co / SiO 2In the catalyst, based on the mass of the catalyst as 100%, preferably the loading amount of Ni is 20% to 25%, the loading amount of Cu is 2% to 2.5%, the loading amount of Fe is 1%, the loading amount of Co is 1%, and the loading amount of K is 0.1%.
[0008] The above Ni-Cu-Fe-Co / SiO 2 The specific preparation method of the catalyst is as follows: using the equal volume impregnation method, iron nitrate, cobalt acetate, nickel nitrate and copper nitrate are dissolved in ethanol, and KNO is added. 3 , stir for 15-30 min, ultrasonically vibrate for 2-4 h, and then add SiO 2 After impregnation for 10 to 12 hours, the mixture was dried at 50 to 80 °C for 6 to 8 hours, and then calcined at 550 to 700 °C for 4 to 6 hours in an air atmosphere, and finally reduced at 550 to 700 °C for 3 to 5 hours in a hydrogen atmosphere to obtain Ni-Cu-Fe-Co / SiO 2 catalyst.
[0009] In the above-mentioned method for catalytic dehydrogenation of methylcyclohexane, the temperature of the dehydrogenation reaction is 350-450° C. and the pressure is 0-0.6 MPa.
[0010] In the above method for catalytic dehydrogenation of methylcyclohexane, the injection amount of methylcyclohexane is 0.1 to 5 mL / min, and the flow rate of nitrogen is 2 to 8 mL / min.
[0011] The beneficial effects of the present invention are as follows:
[0012] The present invention uses Ni-Cu-Fe-Co / SiO 2 The catalyst catalyzes the dehydrogenation of methylcyclohexane to produce toluene and hydrogen. 2 The addition of transition metals Co and Fe to the catalyst changes the surface structure of the carrier and enriches its active sites. At the same time, the carrier has the advantages of high specific surface area, low carbon deposition, and relatively stable alkaline medium. Strong interactions between metals lead to better catalytic effects, increased hydrogen release rate, and maintained hydrogen release stability. The conversion rate of methylcyclohexane reached up to 90.47%, and the selectivity of toluene reached 92.82%. With 102.4mmol g -1 h -1 The stable hydrogen release rate. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 The Ni-Cu / SiO 2 Figure 3. Catalytic performance of the catalyst in the dehydrogenation of methylcyclohexane.
[0014] Figure 2 The Ni-Cu-Ce / SiO2 Figure 3. Catalytic performance of the catalyst in the dehydrogenation of methylcyclohexane.
[0015] Figure 3 The Ni-Cu-Co / SiO 2 Figure 3. Catalytic performance of the catalyst in the dehydrogenation of methylcyclohexane.
[0016] Figure 4 The Ni-Cu-Fe / SiO 2 Figure 3. Catalytic performance of the catalyst in the dehydrogenation of methylcyclohexane.
[0017] Figure 5 The Ni-Cu-Ag / SiO 2 Figure 3. Catalytic performance of the catalyst in the dehydrogenation of methylcyclohexane.
[0018] Figure 6 The Ni-Cu-Mn / SiO 2 Figure 3. Catalytic performance of the catalyst in the dehydrogenation of methylcyclohexane.
[0019] Figure 7 The Ni-Cu-Ce-Co / SiO 2 Figure 3. Catalytic performance of the catalyst in the dehydrogenation of methylcyclohexane.
[0020] Figure 8 The Ni-Cu-Fe-Ce / SiO 2 Figure 3. Catalytic performance of the catalyst in the dehydrogenation of methylcyclohexane.
[0021] Fig. 9 The Ni-Cu-Ce-Ag / SiO 2 Figure 3. Catalytic performance of the catalyst in the dehydrogenation of methylcyclohexane.
[0022] Fig.10 The Ni-Cu-Ag-Co / SiO 2 Figure 3. Catalytic performance of the catalyst in the dehydrogenation of methylcyclohexane.
[0023] Fig.11 The Ni-Cu-Fe-Ag / SiO 2 Figure 3. Catalytic performance of the catalyst in the dehydrogenation of methylcyclohexane.
[0024] Fig.12 The Ni-Cu-Fe-Mn / SiO 2 Figure 3. Catalytic performance of the catalyst in the dehydrogenation of methylcyclohexane.
[0025] Fig.13 The Ni-Cu-Fe-Co / SiO2 Figure 3. Catalytic performance of the catalyst in the dehydrogenation of methylcyclohexane.
[0026] Fig.14 This is a comparison chart of the hydrogen release rates of a series of catalysts of Comparative Examples 1 to 6 in the dehydrogenation of methylcyclohexane.
[0027] Fig.15 It is a comparison chart of hydrogen release rates of the four-metal series catalysts of Example 1 and Comparative Examples 7 to 13 in the dehydrogenation of methylcyclohexane. DETAILED DESCRIPTION
[0028] The present invention is described in detail below with reference to the accompanying drawings and embodiments, but the protection scope of the present invention is not limited to these embodiments.
[0029] Comparative Example 1
[0030] Preparation of Ni-Cu / SiO 2 catalyst
[0031] 1g Ni(NO 3 ) 2 6H 2 O and 0.094g Cu(NO 3 ) 2 6H 2 O was dissolved in 11 mL of ethanol and 0.0025 g of KNO was added 3 , stirred for 30 min, ultrasonically shaken for 2 h, 0.764 g SiO 2 After impregnation for another 10 hours, the mixture was placed in a drying oven at 60°C for 6 hours, ground to 40-60 mesh, and then calcined at 550°C for 4 hours in an air atmosphere using a muffle furnace. 2 The flow rate was 0.03 mL / min, the heating rate was 275.44 °C / min, the temperature was raised to 550 °C, and the reduction was carried out at constant temperature for 4 h to obtain Ni-Cu / SiO 2 The mass content of each component in the catalyst is Ni=20wt%, Cu=2.5wt%, SiO 2 =77.4wt%, and contains auxiliary agent K = 0.1wt%. Passivated with ethanol for later use.
[0032] Comparative Example 2
[0033] Preparation of Ni-Cu-Ce / SiO 2 catalyst
[0034] 1g Ni(NO 3 ) 2 6H 2 O, 0.094 g Cu(NO 3 ) 26H 2 O, 0.031 g Ce(NO 3 ) 3 6H 2 O was dissolved in 11 mL of ethanol and 0.0025 g of KNO was added 3 , stirred for 30 min, ultrasonically shaken for 2 h, 0.764 g SiO 2 After impregnation for another 10 hours, the mixture was placed in a drying oven at 60°C for 6 hours, ground to 40-60 mesh, and then calcined at 550°C for 4 hours in an air atmosphere using a muffle furnace. 2 The flow rate was 0.03 mL / min, the heating rate was 275.44 °C / min, the temperature was raised to 550 °C, and the reduction was carried out at constant temperature for 4 h to obtain Ni-Cu-Ce / SiO 2 The mass content of each component in the catalyst is Ni=20wt%, Cu=2.5wt%, Ce=1wt%, SiO 2 =76.4wt%, and contains auxiliary agent K =0.1wt%. Passivated with ethanol for later use.
[0035] Comparative Example 3
[0036] Preparation of Ni-Cu-Co / SiO 2 catalyst
[0037] 1g Ni(NO 3 ) 2 6H 2 O, 0.094 g Cu(NO 3 ) 2 6H 2 O, 0.03g (CH 3 COO 2 Co was dissolved in 11 mL of ethanol and 0.0025 g of KNO was added. 3 , stirred for 30 min, ultrasonically shaken for 2 h, 0.764 g SiO 2 After impregnation for another 10 hours, the mixture was placed in a drying oven at 60°C for 6 hours, ground to 40-60 mesh, and then calcined at 550°C for 4 hours in an air atmosphere using a muffle furnace. 2 The flow rate was 0.03 mL / min, the heating rate was 275.44 °C / min, the temperature was raised to 550 °C, and the reduction was carried out at constant temperature for 4 h to obtain Ni-Cu-Co / SiO 2 The mass content of each component in the catalyst is Ni=20wt%, Cu=2.5wt%, Co=1wt%, SiO 2 =76.4wt%, and contains auxiliary agent K =0.1wt%. Passivated with ethanol for later use.
[0038] Comparative Example 4
[0039] Preparation of Ni-Cu-Fe / SiO 2 catalyst
[0040] 1g Ni(NO 3 ) 2 6H 2 O, 0.094 g Cu(NO 3 ) 2 6H 2 O, 0.072 g Fe(NO 3 ) 2 6H 2 O was dissolved in 11 mL of ethanol and 0.0025 g of KNO was added 3 , stirred for 30 min, ultrasonically shaken for 2 h, 0.764 g SiO 2 After impregnation for another 10 hours, the mixture was placed in a drying oven at 60°C for 6 hours, ground to 40-60 mesh, and then calcined at 550°C for 4 hours in an air atmosphere using a muffle furnace. 2 The flow rate was 0.03 mL / min, the heating rate was 275.44 °C / min, the temperature was raised to 550 °C, and the reduction was carried out at constant temperature for 4 h to obtain Ni-Cu-Fe / SiO 2 The mass content of each component in the catalyst is Ni=20wt%, Cu=2.5wt%, Fe=1wt%, SiO 2 =76.4wt%, and contains auxiliary agent K =0.1wt%. Passivated with ethanol for later use.
[0041] Comparative Example 5
[0042] Preparation of Ni-Cu-Ag / SiO 2 catalyst
[0043] 1g Ni(NO 3 ) 2 6H 2 O, 0.094 g Cu(NO 3 ) 2 6H 2 O, 0.029g Ag 2 SO 4 Dissolve in 11 mL of deionized water and add 0.0025 g of KNO 3 , stirred for 30 min, ultrasonically shaken for 2 h, 0.764 g SiO 2 After impregnation for another 10 hours, the mixture was placed in a drying oven at 60°C for 6 hours, ground to 40-60 mesh, and then calcined at 550°C for 4 hours in an air atmosphere using a muffle furnace.2 The flow rate was 0.03 mL / min, the heating rate was 275.44 °C / min, the temperature was raised to 550 °C, and the reduction was carried out at constant temperature for 4 h to obtain Ni-Cu-Ag / SiO 2 The mass content of each component in the catalyst is Ni=20wt%, Cu=2.5wt%, Ag=1wt%, SiO 2 =76.4wt%, and contains auxiliary agent K=0.1wt%, and is passivated with ethanol for later use.
[0044] Comparative Example 6
[0045] Preparation of Ni-Cu-Mn / SiO 2 catalyst
[0046] 1g Ni(NO 3 ) 2 6H 2 O, 0.094 g Cu(NO 3 ) 2 6H 2 O, 0.03 g MnSO 4 ·H 2 O was dissolved in 11 mL of deionized water and 0.0025 g of KNO was added 3 , stirred for 30 min, ultrasonically shaken for 2 h, 0.764 g SiO 2 After impregnation for another 10 hours, the mixture was placed in a drying oven at 60°C for 6 hours, ground to 40-60 mesh, and then calcined at 550°C for 4 hours in an air atmosphere using a muffle furnace. 2 The flow rate was 0.03 mL / min, the heating rate was 275.44 °C / min, the temperature was raised to 550 °C, and the reduction was carried out at constant temperature for 4 h to obtain Ni-Cu-Ag / SiO 2 The mass content of each component in the catalyst is Ni=20wt%, Cu=2.5wt%, Mn=1wt%, SiO 2 =76.4wt%, and contains auxiliary agent K=0.1wt%, and is passivated with ethanol for later use.
[0047] Comparative Example 7
[0048] Preparation of Ni-Cu-Ce-Co / SiO 2 catalyst
[0049] 1g Ni(NO 3 ) 2 6H 2 O, 0.094 g Cu(NO 3 ) 2 6H 2 O, 0.03g (CH3 COO 2 Co, 0.031 g Ce(NO 3 ) 3 6H 2 O was dissolved in 11 mL of ethanol and 0.0025 g of KNO was added 3 , stirred for 30 minutes, ultrasonically shaken for 2 hours, and 0.754 g SiO 2 After impregnation for another 10 hours, the mixture was placed in a drying oven at 60°C for 6 hours, ground to 40-60 mesh, and then calcined at 550°C for 4 hours in an air atmosphere using a muffle furnace. 2 The flow rate was 0.03 mL / min, the heating rate was 275.44 °C / min, the temperature was raised to 550 °C, and the reduction was carried out at constant temperature for 4 h to obtain Ni-Cu-Ce-Co / SiO 2 The mass content of each component in the catalyst is Ni=20wt%, Cu=2.5wt%, Co=1wt%, Ce=1wt%, SiO 2 =75.4wt%, and also contains auxiliary agent K=0.1wt%, and is passivated with ethanol for later use.
[0050] Comparative Example 8
[0051] Preparation of Ni-Cu-Fe-Ce / SiO 2 catalyst
[0052] 1g Ni(NO 3 ) 2 6H 2 O, 0.094 g Cu(NO 3 ) 2 6H 2 O, 0.072 g Fe(NO 3 ) 2 6H 2 O, 0.031 g Ce(NO 3 ) 3 6H 2 O was dissolved in 11 mL of ethanol and 0.0025 g of KNO was added 3 , stirred for 30 min, ultrasonically shaken for 2 h, 0.754 g SiO 2 After impregnation for another 10 hours, the mixture was placed in a drying oven at 60°C for 6 hours, ground to 40-60 mesh, and then calcined at 550°C for 4 hours in an air atmosphere using a muffle furnace. 2 The flow rate was 0.03 mL / min, the heating rate was 275.44 °C / min, the temperature was raised to 550 °C, and the reduction was carried out at constant temperature for 4 h to obtain Ni-Cu-Fe-Ce / SiO 2The mass content of each component in the catalyst is Ni=20wt%, Cu=2.5wt%, Fe=1wt%, Ce=1wt%, SiO 2 =75.4wt%, and also contains auxiliary agent K=0.1wt%, and is passivated with ethanol for later use.
[0053] Comparative Example 9
[0054] Preparation of Ni-Cu-Ce-Ag / SiO 2 catalyst
[0055] 1g Ni(NO 3 ) 2 6H 2 O, 0.094 g Cu(NO 3 ) 2 6H 2 O, 0.029g Ag 2 SO 4 、0.031gCe(NO 3 ) 3 6H 2 O was dissolved in 11 mL of deionized water and 0.0025 g of KNO was added 3 , stirred for 30 min, ultrasonically shaken for 2 h, 0.754 g SiO 2 After impregnation for another 10 hours, the mixture was placed in a drying oven at 60°C for 6 hours, ground to 40-60 mesh, and then calcined at 550°C for 4 hours in an air atmosphere using a muffle furnace. 2 The flow rate was 0.03 mL / min, the heating rate was 275.44 °C / min, the temperature was raised to 550 °C, and the reduction was carried out at constant temperature for 4 h to obtain Ni-Cu-Ce-Ag / SiO 2 The mass content of each component in the catalyst is Ni=20wt%, Cu=2.5wt%, Ag=1wt%, Ce=1wt%, SiO 2 =75.4wt%, and also contains auxiliary agent K=0.1wt%, and is passivated with ethanol for later use.
[0056] Comparative Example 10
[0057] Preparation of Ni-Cu-Ag-Co / SiO 2 catalyst
[0058] 1g Ni(NO 3 ) 2 6H 2 O, 0.094 g Cu(NO 3 ) 2 6H 2 O, 0.029g Ag 2SO 4 , 0.03g(CH 3 COO 2 Co was dissolved in 11 mL of ethanol and 0.0025 g of KNO was added. 3 , stirred for 30 min, ultrasonically shaken for 2 h, 0.754 g SiO 2 After impregnation for another 10 hours, the mixture was placed in a drying oven at 60°C for 6 hours, ground to 40-60 mesh, and then calcined at 550°C for 4 hours in an air atmosphere using a muffle furnace. 2 The flow rate was 0.03 mL / min, the heating rate was 275.44 °C / min, the temperature was raised to 550 °C, and the reduction was carried out at constant temperature for 4 h to obtain Ni-Cu-Ag-Co / SiO 2 The mass content of each component in the catalyst is Ni=20wt%, Cu=2.5wt%, Ag=1wt%, Co=1wt%, SiO 2 =75.4wt%, and also contains auxiliary agent K=0.1wt%, and is passivated with ethanol for later use.
[0059] Comparative Example 11
[0060] Preparation of Ni-Cu-Fe-Ag / SiO 2 catalyst
[0061] 1g Ni(NO 3 ) 2 6H 2 O, 0.094 g Cu(NO 3 ) 2 6H 2 O, 0.029g Ag 2 SO 4 、0.072gFe(NO 3 ) 2 6H 2 O was dissolved in 11 mL of deionized water and 0.0025 g of KNO was added 3 , stirred for 30 minutes, ultrasonically shaken for 2 hours, and 0.754 g SiO 2 After impregnation for another 10 hours, the mixture was placed in a drying oven at 60°C for 6 hours, ground to 40-60 mesh, and then calcined at 550°C for 4 hours in an air atmosphere using a muffle furnace. 2 The flow rate was 0.03 mL / min, the heating rate was 275.44 °C / min, the temperature was raised to 550 °C, and the reduction was carried out at constant temperature for 4 h to obtain Ni-Cu-Fe-Ag / SiO 2 The mass content of each component in the catalyst is Ni=20wt%, Cu=2.5wt%, Ag=1wt%, Fe=1wt%, SiO2 =75.4wt%, and also contains auxiliary agent K=0.1wt%, and is passivated with ethanol for later use.
[0062] Comparative Example 12
[0063] 1. Preparation of Ni-Cu-Fe-Mn / SiO 2 catalyst
[0064] 1g Ni(NO 3 ) 2 6H 2 O, 0.094 g Cu(NO 3 ) 2 6H 2 O, 0.03 g MnSO 4 ·H 2 O, 0.072gFe(NO 3 ) 2 6H 2 O was dissolved in 11 mL of deionized water and 0.0025 g of KNO was added 3 , stirred for 30 min, ultrasonically shaken for 2 h, 0.754 g SiO 2 After impregnation for another 10 h, it was placed in a drying oven at 60 °C for 6 h, ground to 40-60 mesh, and then calcined at 550 °C for 4 h in an air atmosphere using a muffle furnace. 2 The flow rate was 0.03 mL / min, the heating rate was 275.44 °C / min, the temperature was raised to 550 °C, and the reduction was carried out at constant temperature for 4 h to obtain Ni-Cu-Ag-Fe / SiO 2 The mass content of each component in the catalyst is Ni=20wt%, Cu=2.5wt%, Ag=1wt%, Fe=1wt%, SiO 2 =75.4wt%, and also contains auxiliary agent K=0.1wt%, and is passivated with ethanol for later use.
[0065] Example 1
[0066] Preparation of Ni-Cu-Fe-Co / SiO 2 catalyst
[0067] 1g Ni(NO 3 ) 2 6H 2 O, 0.094 g Cu(NO 3 ) 2 6H 2 O, 0.072 g Fe(NO 3 ) 2 6H 2 O, 0.03g (CH3 COO 2 Co was dissolved in 11 mL of ethanol and 0.0025 g of KNO was added. 3 , stirred for 30 min, ultrasonically shaken for 2 h, and 0.754 g SiO 2 After impregnation for 10 h, the mixture was placed in a drying oven at 60 °C for 6 h, ground to 40-60 mesh, and then calcined at 550 °C for 4 h in an air atmosphere using a muffle furnace. 2 The flow rate was 0.03 mL / min, the heating rate was 275.44 °C / min, the temperature was raised to 550 °C, and the reduction was carried out at constant temperature for 4 h to obtain Ni-Cu-Fe-Co / SiO 2 The catalyst comprises the following active components: Ni=20wt%, Cu=2.5wt%, Fe=1wt%, Co=1wt%, SiO 2 =75.4wt%, and contains auxiliary agent K=0.1wt%.
[0068] The catalysts obtained in Example 1 and Comparative Examples 1 to 12 were used to catalyze the dehydrogenation of methylcyclohexane, and the performance of each catalyst was evaluated. The dehydrogenation of methylcyclohexane was carried out in a fixed bed continuous flow system (Jiangsu Huaan Keyi), in which a thermocouple was coaxially placed in the middle of the catalyst bed to monitor the gas pressure and temperature. In each experiment, 1 g of the catalyst was sieved to 40 to 60 mesh and mixed with 3 g of SiO 2 (analytical pure) mixed, loaded into the middle part of a stainless steel reactor with an inner diameter of 6mm and a total length of 500mm, methylcyclohexane was injected into the preheater at a rate of 0.1mL / min through an injection pump for vaporization. During the reaction, nitrogen was used as a carrier gas and the injection volume of an inert diluent was 2mL / min. The carrier gas pushed the vaporized methylcyclohexane into the reactor and contacted the catalyst layer for reaction. The reaction temperature was 350℃ and the reaction pressure was 0.2MPa. After condensation and separation, the reaction products were analyzed by gas chromatography GC-7700 (Shanghai Tianmei) equipped with an ON-WAX capillary column (50m×0.32mm×1μm) and a flame ionization detector (FID).
[0069] Depend on Figures 1 to 15 It can be seen that during the 6h evaluation process, the Ni-Cu / SiO 2 The catalyst has a stable conversion rate of methylcyclohexane at around 59.44%, a stable selectivity of toluene at around 98.9%, and a stable hydrogen release rate at 80 mmol g -1 h -1 The catalyst has the problem of low methylcyclohexane conversion rate, and the hydrogen release rate only reaches the general level of dehydrogenation catalyst; the Ni-Cu-Ce / SiO2 The catalyst, the conversion rate of methylcyclohexane gradually increased to 56.58%, the selectivity of toluene has been stable at about 96.9%, and the hydrogen release rate gradually increased to 77.5mmolg -1 h -1 The catalyst has the problem of insufficient conversion rate of methylcyclohexane, unstable hydrogen release rate and induction period during the 6h evaluation process; the Ni-Cu-Co / SiO 2 The catalyst showed that the conversion rate of methylcyclohexane gradually increased to about 78.53%, the selectivity of toluene gradually decreased from 95.44% to 91.70%, and the hydrogen release rate gradually increased to 101mmol g -1 h -1 The catalyst also has the problem that the conversion rate of methylcyclohexane is not high enough, the hydrogen release rate is not stable enough during the 6h evaluation process, and there is an induction period problem; the Ni-Cu-Fe / SiO 2 The conversion rate of methylcyclohexane gradually increased to 62.71% and then decreased to 48.41%. The selectivity of toluene remained stable at around 99.20%. The hydrogen release rate gradually increased to 88 mmol g -1 h -1 The catalyst also has the problem that the conversion rate of methylcyclohexane is not high enough, the hydrogen release rate is not stable enough during the 6h evaluation process, and there is an induction period problem; the Ni-Cu-Ag / SiO 2 The catalyst showed that the conversion rate of methylcyclohexane gradually increased from 5.88% to 80.39%, and then decreased to 72.06%. The selectivity of toluene increased from 91.54% to about 98.61%, and then stabilized. The hydrogen release rate increased from 7.8 mmol g -1 h -1 Gradually increased to 105.9mmolg -1 h -1 The catalyst has a long induction period. 2 The catalyst showed that the conversion of methylcyclohexane increased from 4.64% to 94.79%, the selectivity of toluene increased from 69% to 94.53% and then decreased to 87.22%, and the hydrogen release rate increased from 4.53 mmol g -1 h -1 Gradually increased to 118.7 mmol g -1 h -1 The catalyst has a long induction period. 2The conversion rate of methylcyclohexane showed a volcanic pattern, rising first and then falling. The best conversion rate was 54.11%. The selectivity of toluene was stable at around 98.41%. The hydrogen release rate was the highest in 3 hours, which was 79 mmol g -1 h -1 The catalyst has a low hydrogen release rate. 2 The catalyst showed that the conversion of methylcyclohexane gradually increased from 3.62% to 89.72% and then decreased to 72.61%. The selectivity of toluene gradually increased from 68.38% to 90%. The hydrogen release rate increased from 39.8 mmol g -1 h -1 Gradually increased to 88 mmol g -1 h -1 , the catalyst also has the problem of a long induction period; using the Ni-Cu-Ag-Ce / SiO 2 The catalyst, the conversion of methylcyclohexane decreased from 45.98% to 22.36%, the selectivity of toluene was stable at 99.42%, and the maximum hydrogen release rate was 65mmolg -1 h -1 , and then dropped to 33mmol g -1 h -1 The catalyst has the problem of unstable conversion rate and hydrogen release rate; the Ni-Cu-Ag-Co / SiO 2 The catalyst showed that the conversion of methylcyclohexane first increased from 58.88% to 92.74%, and then slowly decreased to 87.17%. The selectivity of toluene slowly decreased from 80.92% to 54.59%, and the hydrogen release rate increased from 27.7 mmol g - 1 h -1 Gradually decreased to 8 mmol g -1 h -1 The catalyst has a low hydrogen release rate. 2 The selectivity of methylcyclohexane decreased from 99.53% to 84.42% over the catalyst. The conversion rate of toluene increased from 2.64% and then decreased by 0.83%, with the highest being only 37.6%. The hydrogen release rate increased first and then decreased, with the highest being 77.5mmolg -1 h -1 The catalyst has the problems of low hydrogen release rate and low conversion rate. 2The conversion rate of methylcyclohexane increased from 52% to 70.7%, then decreased to 61.36%, and then gradually increased to 70.93%. The selectivity of toluene was close to 100%, and the hydrogen release rate increased from 72.76 mmol g -1 h -1 Increased to 99.21mmolg -1 h -1 Later it dropped to 85.98mmol g -1 h -1 The catalyst has poor stability and also has an induction period; while the Ni-Cu-Fe-Co / SiO 2 The conversion rate and selectivity of methylcyclohexane showed a volcanic pattern, with one side rising and the other side falling. The conversion rate of methylcyclohexane reached 90.47% at the highest, the selectivity of toluene reached 92.82%, and the hydrogen release rate was basically stable at 102.4mmol g -1 h -1 .
[0070] It can be seen from the above that compared with the nickel-copper system, the trimetallic alloy has a more active hydrogen desorption rate. The trimetallic catalyst has a hydrogen release rate of 105.9 mmol g -1 h -1 The hydrogen release rate is high and shows an upward trend. Compared with tri-metal, tetra-metal alloy has improved the conversion rate and selectivity by one level. The tetra-metal catalyst Ni-Cu-Fe-Co / SiO 2 The conversions were 74.49% and 90.47% at 92.8% and 80.0% toluene selectivities, respectively, with 102.4 mmol g -1 h -1 The stable hydrogen release rate of Ni-Cu / SiO 2 Only 80 mmol g -1 h -1 A stable hydrogen release rate of about .
Claims
1. A method for dehydrogenating methylcyclohexane using a high entropy alloy supported catalyst, characterized in that: A fixed bed reactor is used to gasify methylcyclohexane and then pass it into a catalyst bed under the drive of nitrogen, where it undergoes a dehydrogenation reaction under the action of a Ni-Cu-Fe-Co / SiO2 catalyst to obtain toluene and hydrogen. The Ni-Cu-Fe-Co / SiO2 catalyst is prepared by using SiO2 as a carrier, adopting an equal volume impregnation method to load active components Ni, Cu, Fe, Co and an auxiliary agent K, and undergoing high-temperature calcination and hydrogen reduction; taking the mass of the catalyst as 100%, the loading amount of Ni is 10% to 30%, the loading amount of Cu is 1% to 3%, the loading amount of Fe is 0.5% to 1.5%, the loading amount of Co is 0.5% to 1.5%, and the loading amount of K is 0.05% to 0.15%.
2. The method for dehydrogenating methylcyclohexane using a high entropy alloy supported catalyst according to claim 1, characterized in that: Taking the mass of the catalyst as 100%, the loading amount of Ni is 20% to 25%, the loading amount of Cu is 2% to 2.5%, the loading amount of Fe is 1%, the loading amount of Co is 1%, and the loading amount of K is 0.1%.
3. The method for dehydrogenating methylcyclohexane using a high entropy alloy supported catalyst according to claim 1 or 2, characterized in that: The preparation method of the Ni-Cu-Fe-Co / SiO2 catalyst is as follows: using an equal volume impregnation method, ferric nitrate, cobalt acetate, nickel nitrate and copper nitrate are dissolved in ethanol, and KNO3 is added, stirred for 15 to 30 minutes, ultrasonically shaken for 2 to 4 hours, and then SiO2 is added and impregnated for 10 to 12 hours, and then dried at 50 to 80°C for 6 to 8 hours, and then calcined at 550 to 700°C in an air atmosphere for 4 to 6 hours, and finally reduced at 550 to 700°C in a hydrogen atmosphere for 3 to 5 hours to obtain the Ni-Cu-Fe-Co / SiO2 catalyst.
4. The method for dehydrogenating methylcyclohexane using a high entropy alloy supported catalyst according to claim 1, characterized in that: The temperature of the dehydrogenation reaction is 350-450° C. and the pressure is 0-0.6 MPa.
5. The method for dehydrogenating methylcyclohexane using a high entropy alloy supported catalyst according to claim 1, characterized in that: The injection volume of the methylcyclohexane is 0.1 to 5 mL / min, and the flow rate of the nitrogen is 2 to 8 mL / min.